Preparation method of copper-clad ceramic substrate

Through direct bonding of copper slurry to ceramic substrates and steel screen printing technology, the problems of complex preparation process and insufficient binding force of traditional copper clad ceramic substrates are solved, and the preparation of copper clad ceramic substrates with simple process, low cost and high reliability are achieved.

CN119815704AActive Publication Date: 2025-04-11BEIJING UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411915242.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The preparation process of traditional copper clad ceramic substrates is complex and costly, and tiny defects on the surface of the ceramic and copper sheets may lead to hollows in the brazing interface, affecting the bonding strength.

Method used

The direct bonding method between copper slurry and ceramic substrate is adopted to form a patterned copper clad layer on the ceramic substrate through steel screen printing technology. The process is simple and the sintering temperature is lower, achieving a good combination of copper and ceramic substrate.

Benefits of technology

It realizes simple process, high thermal conductivity, good moldability and excellent bonding force between copper and ceramic substrates, reduces preparation cost and residual stress, and improves the flatness and reliability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119815704A_ABST
    Figure CN119815704A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad ceramic substrates, in particular to a preparation method of a copper-clad ceramic substrate. Comprising the following steps: S1, carrying out surface treatment on a ceramic substrate; s2, designing a corresponding steel mesh pattern according to a circuit design requirement, and manufacturing a steel mesh; s3, directly printing the copper slurry on the processed ceramic substrate in a steel mesh printing manner to form a patterned copper-clad layer, and drying the patterned copper-clad layer in a nitrogen atmosphere; s4, repeating the step S3 for multiple times to obtain a printed sample; and S5, sintering the printed sample, and then polishing and cleaning to obtain the copper-clad ceramic substrate. According to the method, the graphical copper-clad layer can be directly obtained through a steel mesh printing means, the tedious steps of welding copper foil through brazing filler metal and subsequent etching are avoided, the process is simple, good formability is achieved, and the binding force between the prepared finished product copper-clad layer and the ceramic substrate is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-clad ceramic substrates, and in particular to a preparation method of a copper-clad ceramic substrate. Background Art

[0002] With the continuous development of aerospace, electric vehicles and other fields, the requirements for core power devices are gradually increasing, and the third-generation semiconductors have gradually received more and more research and attention. The third-generation semiconductors have a higher operating junction temperature and can still maintain good operating performance above 350°C. Copper-clad ceramic substrates in high-power application scenarios require higher copper thickness and higher temperature reliability to ensure that the device does not fail prematurely.

[0003] At present, the preparation of copper-clad ceramic substrates mainly includes direct copper plating (DPC) process, direct copper bonding (DBC) process, active metal brazing (AMB) process and other methods. Among them, the active metal brazing (AMB) process mainly places the active brazing material on the surface of the ceramic carrier by thick film printing, and then places the copper foil layer on both sides of the ceramic carrier covered with metal solder to form a copper-brazing material-ceramic-brazing material-copper structure, and then vacuum sintering is performed to make the ceramic, brazing material and copper foil tightly welded, and then the product is made through processes such as exposure, development, etching and surface treatment.

[0004] The traditional AMB process is relatively complex and requires precise process control, resulting in high costs. In addition, any tiny defects on the surface of the ceramic and copper sheets may cause voids in the soldering interface, affecting the bonding strength. Therefore, the development of a new type of copper-clad ceramic substrate that can achieve direct bonding between the copper slurry and the ceramic substrate to form a patterned copper-clad layer has become a research hotspot in the field of electronic packaging materials, with simple process, high thermal conductivity, good formability, and excellent bonding between copper and ceramic substrates.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a copper-clad ceramic substrate, which can realize direct bonding between a copper slurry and a ceramic substrate to form a patterned copper-clad layer, has a simple process, and has good formability, and the prepared finished copper-clad layer has a strong bonding force with the ceramic substrate.

[0007] The present invention provides a method for preparing a copper-clad ceramic substrate, comprising the following steps:

[0008] S1. Surface treatment of the ceramic substrate, including cleaning and removing impurities to enhance the bonding strength between the copper slurry and the ceramic substrate;

[0009] S2. Design the corresponding steel mesh pattern and make the steel mesh according to the circuit design requirements;

[0010] S3. The copper paste is directly printed on the treated ceramic substrate by steel screen printing to form a patterned copper coating, and then dried under a nitrogen atmosphere;

[0011] S4. Repeat step S3 several times to obtain a printed sample; prepare thick copper by double-sided printing and drying several times;

[0012] S5. The printed sample is sintered to achieve close bonding between the copper clad layer and the ceramic substrate; after sintering, post-processing steps such as grinding and cleaning are performed to remove surface impurities and improve surface flatness, and finally a copper-clad ceramic substrate is obtained.

[0013] Preferably, step S2 comprises:

[0014] S21. Design the corresponding steel mesh pattern according to the requirements of the circuit design, which includes determining the layout of the circuit, the location of the components, the direction of the line, etc. The design of the steel mesh pattern needs to take into account the function, performance and assembly convenience of the circuit;

[0015] S22. Selecting a suitable thickness of the steel sheet, the thickness of the steel sheet determines the thickness of the copper clad layer, thereby affecting the performance of the copper clad ceramic substrate;

[0016] S23. According to the designed steel mesh pattern, the required steel mesh is made by laser engraving.

[0017] Preferably, the copper slurry used in step S3 is prepared by the following method:

[0018] (1) acid washing the copper powder particles to obtain deoxidized copper particles;

[0019] (2) coating the deoxidized copper particles with a binder to obtain coated copper particles;

[0020] (3) uniformly mixing a plasticizer, a leveling agent, a dispersant, a coupling agent, a curing agent, a sintering temperature regulator and an organic solvent to obtain an organic solvent system;

[0021] (4) Mixing and stirring the coated copper particles with an organic solvent system to obtain the copper slurry.

[0022] Preferably, the acid used for pickling in step (1) is one of dilute sulfuric acid, hypophosphorous acid, and hypochlorous acid; more preferably dilute sulfuric acid or hypochlorous acid; the shape of the copper powder particles used is spherical or flaky, and the particle size ranges from 100 to 2200 nm; more preferably 300 to 1500 nm, and the particle size can be 300 nm, 400 nm, 500 nm, 800 nm, 1000 nm, or 1200 nm.

[0023] Preferably, the adhesive in step (2) is selected from at least one of polyvinyl alcohol, polyacrylate, polyvinyl acetate, polyvinyl butyral, and methyl cellulose; more preferably, polyvinyl butyral or polyacrylate.

[0024] Preferably, the mass percentage of each component in the organic solvent system obtained in the step (3) is as follows: 1%-5% plasticizer, 0.5%-3% leveler, 0.5%-3% dispersant, 0.2%-1% coupling agent, 0.5%-3% curing agent, 0.2%-1% sintering temperature regulator, and 91%-96% organic solvent. There is no strict restriction on the mixing method of the organic solvent system, as long as it can be mixed evenly, for example, magnetic stirring can be performed for 1-3 hours.

[0025] Preferably, the plasticizer used in step (3) is at least one of citrate esters, terephthalate esters and cyclohexane dicarboxylates;

[0026] The leveling agent is one or more of polyethylene oxide, polyether-modified silicone, polyether polyol, and polyurethane;

[0027] The dispersant is at least one selected from unsaturated fatty acids having carbon atoms greater than or equal to 12 and less than or equal to 24;

[0028] The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, phosphate, and polyethyleneimine;

[0029] The curing agent is one or more of xylene peroxide, benzoyl peroxide, phenylenediamine, dichloroaniline, and diethylenetriamine;

[0030] The sintering temperature regulator is one or more of sodium chloride, sodium sulfate, ammonium chloride, and a trace amount of rare earth metals (such as yttrium and cerium);

[0031] The organic solvent is at least one alcohol organic solvent.

[0032] Preferably, the dispersant is selected from at least one of linoleic acid and linolenic acid; and the organic solvent is selected from at least one of ethanol, ethylene glycol, propylene glycol, glycerol and diethylene glycol.

[0033] In the organic solvent system, plasticizers are used to improve the fluidity and flexibility of the slurry to facilitate printing and molding; leveling agents are used to ensure the uniformity of the slurry thickness during the printing process; dispersants are used to prevent copper particles from agglomerating during the preparation and printing of copper slurry; coupling agents are used to improve the adhesion between the copper slurry and the ceramic substrate; curing agents are used to promote the hardening or curing process of the slurry and improve the strength of the copper coating; sintering temperature regulators can adjust the sintering temperature of copper and promote the expansion or molding of copper particles to make the sintering process more uniform; organic solvents are used to adjust the viscosity of the copper slurry.

[0034] Preferably, the stirring in step (4) is carried out using a vacuum degassing machine for 10-40 minutes.

[0035] Preferably, when printing the copper paste on the ceramic substrate in step S3, the copper paste is first printed on the front side of the ceramic substrate and dried, and then printed on the back side of the ceramic substrate and dried.

[0036] Preferably, the sintering temperature in step S5 is 400-600° C., the holding time is 15-45 minutes, and the sintering atmosphere is an inert atmosphere.

[0037] In summary, the present invention has the following advantages:

[0038] Traditional copper-clad ceramic substrates are basically prepared by connecting copper foil and ceramic substrates through solder. The disadvantages are that the required sintering temperature is relatively high (above 800°C), and processes such as exposure, development, etching and surface treatment are required to obtain imaged copper-clad ceramics.

[0039] The technical solution of the present invention adds a plasticizer, a curing agent and a binder to prepare a copper paste with certain plastic formability, thereby ensuring the quality of multiple printings of the copper paste on the ceramic substrate, preventing the printed layer from collapsing, and achieving good control of the formability. At the same time, the present invention adopts a method of printing and drying repeatedly to achieve printing with a thickness of more than 800 μm, so that a graphic copper coating can be directly obtained by steel screen printing, avoiding the cumbersome steps of soldering copper foil and subsequent etching.

[0040] The sintering temperature of the copper-clad ceramic substrate prepared by the present invention is lower (400°C-600°C), so that the residual stress of the final product is lower and the flatness is better. The added binder enables the copper slurry to be better combined with the ceramic substrate under low-temperature sintering, effectively improving the connection quality and enhancing the reliability of the copper-clad ceramic substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is a flow chart of the preparation of the copper-clad ceramic substrate in Example 1 of the present invention;

[0043] Figure 2 This is a flow chart of the preparation of copper slurry in Example 1 of the present invention;

[0044] Figure 3 Schematic diagram of the structure of the copper-clad ceramic substrate prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0047] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0048] Example 1

[0049] A method for preparing a copper-clad ceramic substrate, such as Figure 1 As shown, the specific process is as follows:

[0050] S1. Perform ultrasonic cleaning on the ceramic substrate to remove surface impurities.

[0051] S2. Steel mesh pattern design and production

[0052] S21. Design the corresponding steel mesh pattern according to the requirements of the circuit design, which includes determining the layout of the circuit, the location of the components, the direction of the line, etc. The design of the steel mesh pattern needs to take into account the function, performance and assembly convenience of the circuit;

[0053] S22. Select a steel sheet having a thickness of 300 μm;

[0054] S23. According to the designed steel mesh pattern, the required steel mesh is made by laser engraving.

[0055] S3.Stencil printing and drying

[0056] Pour the copper slurry into the hopper of the steel screen printer, place the treated ceramic substrate on the platform of the printer, print the copper slurry on the front of the ceramic substrate by the steel screen printer to form a patterned copper coating, and dry it under the protection of a nitrogen atmosphere, then print the copper slurry on the back of the ceramic substrate by the steel screen printing method, and dry it under the protection of a nitrogen atmosphere;

[0057] S4. Repeat step S3, perform double-sided printing and drying three times, to achieve the preparation of thick copper on the ceramic substrate, and obtain a printed sample;

[0058] S5. The printed samples were placed in a drying oven for sintering, and the temperature was raised to 400°C at a rate of 3°C / min and maintained for 30 min. The sintering atmosphere was nitrogen. After sintering, the samples were taken out for polishing and cleaning to remove surface impurities, and a copper-clad ceramic substrate (such as Figure 3 shown).

[0059] The copper slurry used in step S3 is prepared by the following method (eg Figure 2 shown):

[0060] (1) copper powder particles (particle size 300 nm) were mixed with hypochlorous acid solution, ultrasonically treated for 10 min, centrifuged to remove the supernatant, then anhydrous ethanol was added, ultrasonically treated for 6 min, and centrifuged to remove the supernatant to obtain deoxidized copper particles;

[0061] (2) mixing the deoxidized copper particles with a polyvinyl butyral ethanol solution, wherein the mass ratio of polyvinyl butyral to ethanol is 1:99, ultrasonically treating for 90 minutes, and centrifuging to remove the supernatant to obtain binder-coated copper particles; mixing the binder-coated copper particles with the ethanol solution, ultrasonically treating for 10 minutes, and centrifuging to remove the supernatant to obtain coated copper particles;

[0062] (3) The following raw materials in percentage by weight: 2% tributyl citrate, 1.5% polyethylene oxide, 0.5% linolenic acid, 0.3% γ-aminopropyltriethoxysilane, 1.5% xylene peroxide, 0.5% sodium chloride, and 93.7% ethylene glycol were mixed and magnetically stirred for 3 hours to obtain an organic solvent system;

[0063] (4) After mixing the coated copper particles with the organic solvent system, the mixture was stirred in a vacuum degassing machine for 30 minutes to obtain a copper slurry.

[0064] Example 2

[0065] A method for preparing a copper-clad ceramic substrate, the specific process is as follows:

[0066] S1. Perform ultrasonic cleaning on the ceramic substrate to remove surface impurities.

[0067] S2. Steel mesh pattern design and production

[0068] S21. Design the corresponding steel mesh pattern according to the requirements of the circuit design, which includes determining the layout of the circuit, the location of the components, the direction of the line, etc. The design of the steel mesh pattern needs to take into account the function, performance and assembly convenience of the circuit;

[0069] S22. Select a steel sheet having a thickness of 300 μm;

[0070] S23. According to the designed steel mesh pattern, the required steel mesh is made by laser engraving.

[0071] S3.Stencil printing and drying

[0072] Pour the copper slurry into the hopper of the steel screen printer, place the processed ceramic substrate on the platform of the printer, print the copper slurry on the front of the ceramic substrate by the steel screen printer to form a patterned copper coating, and dry it under the protection of a nitrogen atmosphere. Then, print the copper slurry on the back of the ceramic substrate by the steel screen printing method, and dry it under the protection of a nitrogen atmosphere.

[0073] S4. Repeat step S3, perform double-sided printing and drying three times, and realize the preparation of thick copper on the ceramic substrate.

[0074] S5. Place the printed sample in a drying furnace for sintering, raise the temperature to 500°C at a rate of 3°C / min, and maintain for 30 minutes. The sintering atmosphere is nitrogen. After sintering, take out the sample for polishing and cleaning to remove surface impurities to obtain a copper-clad ceramic substrate.

[0075] The copper slurry used in step S3 is prepared by the following method:

[0076] (1) copper powder particles (particle size 300 nm) were mixed with a dilute sulfuric acid solution, ultrasonically treated for 10 min, and the supernatant was removed by centrifugation. Anhydrous ethanol was then added, ultrasonically treated for 6 min, and the supernatant was removed by centrifugation to obtain deoxidized copper particles;

[0077] (2) mixing the above-mentioned deoxidized copper particles with a polyacrylate ethanol solution, wherein the mass ratio of polyacrylate to ethanol is 1:99, ultrasonically treating for 90 minutes, and centrifuging to remove the supernatant to obtain binder-coated copper particles; mixing the binder-coated copper particles with an ethanol solution, ultrasonically treating for 10 minutes, and centrifuging to remove the supernatant to obtain coated copper particles;

[0078] (3) The following raw materials in percentage by weight: 2% of acetyl tributyl citrate, 1.5% of polyurethane, 0.5% of linoleic acid, 0.3% of polyethyleneimine, 2% of benzoyl peroxide, 0.5% of sodium sulfate, and 93.2% of propylene glycol were mixed and magnetically stirred for 3 hours to obtain an organic solvent system;

[0079] (4) After mixing the coated copper particles with the organic solvent system, the mixture was stirred in a vacuum degassing machine for 30 minutes to obtain a copper slurry.

[0080] Comparative Example 1

[0081] A method for preparing a copper-clad ceramic substrate, the technical scheme of which is basically the same as that of Example 1, except that: in the copper slurry preparation process used in step S3, no plasticizer tributyl citrate, curing agent xylene peroxide and sintering temperature regulator sodium chloride are added.

[0082] Comparative Example 2

[0083] A method for preparing a copper-clad ceramic substrate, the technical scheme of which is basically the same as that of Example 2, except that: in the preparation process of the copper slurry used in step S3, no plasticizer tributyl acetyl citrate, no curing agent benzoyl peroxide and no sintering temperature regulator sodium sulfate are added.

[0084] The experiments show that the copper paste prepared in Comparative Example 1-2 has poor formability, cannot maintain a graphical shape after screen printing, has a collapsed printed layer, and is not firmly bonded to the ceramic substrate after sintering at 800°C.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a copper-clad ceramic substrate, characterized in that: The following steps are involved: S1. Surface treatment of ceramic substrate; S2. Design the corresponding steel mesh pattern and make the steel mesh according to the circuit design requirements; S3. The copper paste is directly printed on the treated ceramic substrate by steel screen printing to form a patterned copper coating, and then dried under a nitrogen atmosphere; S4. Repeat step S3 several times to obtain a printed sample; S5. The printed sample is sintered, polished, and cleaned to obtain a copper-clad ceramic substrate.

2. The preparation method according to claim 1, characterized in that: The copper slurry used in step S3 is prepared by the following method: (1) acid washing the copper powder particles to obtain deoxidized copper particles; (2) coating the deoxidized copper particles with a binder to obtain coated copper particles; (3) uniformly mixing a plasticizer, a leveling agent, a dispersant, a coupling agent, a curing agent, a sintering temperature regulator and an organic solvent to obtain an organic solvent system; (4) Mixing and stirring the coated copper particles with an organic solvent system to obtain the copper slurry.

3. The preparation method according to claim 2, characterized in that: The acid used for pickling in step (1) is one of dilute sulfuric acid, hypophosphorous acid and hypochlorous acid; the shape of the copper powder particles used is spherical or flaky, and the particle size ranges from 100 to 2200 nm.

4. The preparation method according to claim 2, characterized in that: The binder in step (2) is selected from at least one of polyvinyl alcohol, polyacrylate, polyvinyl acetate, polyvinyl butyral, and methyl cellulose.

5. The preparation method according to claim 2, characterized in that: The mass percentage of each component in the organic solvent system obtained in the step (3) is as follows: 1%-5% plasticizer, 0.5%-3% leveler, 0.5%-3% dispersant, 0.2%-1% coupling agent, 0.5%-3% curing agent, 0.2%-1% sintering temperature regulator, and 91%-96% organic solvent.

6. The preparation method according to claim 5, characterized in that: The plasticizer used in step (3) is at least one of citrate esters, terephthalate esters and cyclohexane dicarboxylates; The leveling agent is one or more of polyethylene oxide, polyether-modified silicone, polyether polyol, and polyurethane; The dispersant is at least one selected from unsaturated fatty acids having carbon atoms greater than or equal to 12 and less than or equal to 24; The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, phosphate, and polyethyleneimine; The curing agent is one or more of xylene peroxide, benzoyl peroxide, phenylenediamine, dichloroaniline, and diethylenetriamine; The sintering temperature regulator is one or more of sodium chloride, sodium sulfate, ammonium chloride, and rare earth metals; The organic solvent is at least one alcohol organic solvent.

7. The preparation method according to claim 6, characterized in that: The dispersant is selected from at least one of linoleic acid and linolenic acid; the organic solvent is selected from at least one of ethanol, ethylene glycol, propylene glycol, glycerol and diethylene glycol.

8. The preparation method according to claim 2, characterized in that: The stirring in step (4) is carried out by using a vacuum degassing machine for 10-40 minutes.

9. The preparation method according to claim 1, characterized in that: When the copper paste is printed on the ceramic substrate in step S3, it is first printed on the front side of the ceramic substrate and dried, and then printed on the back side of the ceramic substrate and dried.

10. The preparation method according to claim 1, characterized in that: The sintering temperature in step S5 is 400-600° C., the holding time is 15-45 minutes, and the sintering atmosphere is an inert atmosphere.

Citation Information

Patent Citations

  • Conductive silver paste with low sintering temperature, preparation method and application thereof

    CN110534229A

  • Preparation method of copper paste printed circuit board

    CN112062607A

  • Slurry for ceramic copper-clad part, ceramic copper-clad part and preparation method and application of ceramic copper-clad part

    CN117326886A

  • Manufacture of ceramic circuit board

    JP1994204645A